A Study on Antimicrobial Activities of Essential Oils of Different Cultivars of Lemongrass (Cymbopogon flexuosus) - Ashish Kumar Gupta, Ritam Muhury, Deepak Ganjewala (Tabriz University of Medical Sciences, 2016)
Background: Cymbopogon flexuosus popularly known as lemongrass provides a lemon scented essential oil which is widely used in flavour and fragrance, perfumery, food and pharmaceuticals. The aim of the present study was to assess antimicrobial activities of essential oils of three lemongrass cultivars viz., Pragati, Praman and Suvarna. Methods: Essential oils were isolated from one month old plants by hydro-distillation in mini Clevenger apparatus for 2 h. Antimicrobial activities were determined by agar well diffusion method Results: Lemongrass oils exhibited strong antimicrobial activity against all the microbes except E coli. Mean inhibition zone diameter (mm) against bacteria was ranged 27-38 mm. B. Subtilis was the most sensitive bacterium to all essential oils. Essential oils also showed strong antifungal effects against both A. niger and C. albicans with mean inhibition zone diameter (mm) values 20-26 and 27-29 mm, respectively. Statistical analyses revealed that antimicrobial activity shown by essential oils were significant (p < 0.05) against all microorganisms except B. subtilis and C. albicans (p >> 0.05). Conclusion: The study revealed strong antimicrobial potential of the essential oil against pathogenic microbial strains which may be of high clinical importance in future.